ANALISIS RADIUS AMAN AKIBAT KEGAGALAN STRUKTUR SUDU SKEA 50 KW PADA SAAT BEROPERASI - Atmadi, Sulistyo; Fitroh, Ahmad Jamaludin (BRIN Publishing, 2010)
Analysis on the safe radius of a blade structural failure during operation, is studied on this paper. The particular blade under analysis is the SKEA 50 kW LAPAN. The rotor is installed at 18 m height. The analysis is based on the modified straight motion and rotational momentum formulation. The result showed that at the maximum design rotational speed of 80 rpm, the blade would be thrown out of it centre to 73 m horizontally, and 35 m vertically above the ground. On the other hand, the failure at the root of the blade would be thrown and spinned at its centre of mass at the speed of 145 rpm.